STO LET SLOVENISTIKY NA UNIVERZITĚ KARLOVĚ V PRAZE. Ur. Alenka Jensterle - Doležalová, Jasna Honzak Jahić, Andrej Šurla: Praha: Filozofická fakulta Univerzity Karlovy, 2014. 569 str. - Koprivnikar, Aljaž (Slavia Centralis, 2020)
The article presents the monograph Sto let slovenistiky na Univerzitě Karlově v Praze (One Hundred Years of Slovene Studies at Charles University in Prague), which was created as a result of a symposium held in 2014 by Alenka Jensterle - Doležal, Jasna Honzak Jahić and Andreja Šurla on the occasion of the 100th anniversary of Slovene studies at Charles University.